Visket Jatra: From The Political Aspect - Kayastha, Balaram (Voice of History, 2023)
Visket Jatra is one of the famous festivals of Bhaktapur area, which is being celebrated every year with Mesha Sankranti (Aries Solstice) as the focal point. Many kinds of legends are also prevalent among the people regarding this festival. But recent studies have shown that there is no truth in some of these legends. What exactly is Visket Jatra? In this regards it is difficult to interprate it in the true sense by looking at it from a single angle. For this, it is necessary to have study and analysis from various aspects like religious, cultural, social, political etc. From a religious point of view, this Jatra procession is a procession of Bhairav, the chief deity of Bhaktapur city and his consert Bhairavi. Similarly, at the Tantrik level, this Jatra (procession) can be taken as a symbol of mutual intercourse between the two. The Jatra also seems to have a role to play in entertaining the general public. In this way, from the very beginning at the political level, this Jatra was a symbol of good relations between the king and the people. However, there are also rumors that such Jatras (festivals) have been introduced in the name of religion to divert public attention from political issues. But in the case of Bhaktapur, the relationship between the king and the people here have always been sweet and cordial, many historical contexts make this clear. The same intimate relationship used to be revealed in the Visket Jatra. The Jatras festivals has not only the religious or cultural significance but it also has political aspect. This article is prepared in descriptive, analytical and comparative study method. And main conclusion of this study is that how, despite being a traditional Jatra, this Jatra has been going on continuously till today, it has been highlighted that the state or the government also has an important role in this, as well as people’s support and participation.